Implementation of The Make A Match Type Cooperative Learning Model to Improve The Learning Outcomes of SMP Negeri 1 Kolaka - Marwiah Marwiah (Journal of Biological Science and Education, 2022)
The main task of the teacher is to teach students, namely to condition students to learn actively so that their potential can develop properly. This study aims to improve the learning outcomes of class VIII A SMP Negeri 1 Kolaka on the subject matter of motion in plants. This research is a classroom action research (PTK) using two cycles. In this CAR, the subjects of the study were students of class VIII. a which consisted of 22 students with 13 female students and 9 male students.  The research instrument uses a test instrument to measure students' cognitive learning outcomes.  Data were analyzed descriptively using percentage techniques.  Based on the research results, it can be seen that the average student learning outcome in cycle 1 is 74.7 and in cycle 2 is 79.4. Based on the results of the study, it can be concluded that the application of the make-a-match type of cooperative learning model to the subject of motion in plants can improve student learning outcomes. Keywords: Make A Match, Learning outcome